PENGARUH PENGGUNAAN MEDIA KAHOOT DALAM PEMBELAJARAN IPAS TERHADAP HASIL BELAJAR SISWA DI SDN LAWANGAN DAYA 3 PAMEKASAN - Nadia Ramadhani; Nurul Khomisah; Nur Indah Putri Ayu Pratama Roda’i; Ika Dian Rahmawati (INOVASI : Jurnal Ilmiah Pengembangan Pendidikan, 2026)
The use of interactive learning media such as Kahoot is an innovation to improve the quality of learning in elementary schools. This study aimed to determine the effect of using Kahoot media in Natural and Social Sciences learning on student learning outcomes in the food chain topic. The research employed a quantitative approach with a One-Group Pretest-Posttest design. The subjects were 18 fifth-grade students of State Elementary School Lawangan Daya 3 Pamekasan. The instrument consisted of ten multiple-choice questions for both pretest and posttest. Data analysis was performed using a paired sample t-test with SPSS software. The results showed that the average pretest score was 41.67, which increased to 73.89 in the posttest, a gain of 32.22 points. The statistical test revealed a t-value of 10.447, higher than the t-table value of 2.1098, with a significance level of 0.000, leading to the acceptance of the alternative hypothesis. Therefore, there is a significant effect of using Kahoot media in Natural and Social Sciences learning on student learning outcomes. The use of Kahoot not only improves cognitive learning outcomes but also creates an active, enjoyable, and motivating learning atmosphere. Kahoot media is recommended as an alternative technology-based learning media in elementary schools.